MEMBANGUN KESADARAN LITERASI INFORMASI DALAM KONTEKS PENYELESAIAN TUGAS AKHIR SANTRI DI PONDOK PESANTREN SUMATERA THAWALIB PARABEK: SUATU PENELITIAN TINDAKAN PARTISIPATIF - Yunita, Rahmi; Muntashir, Muntashir; Fauzi, Fauzi; Fitri, Inda; Erida, Erida; Zulkifli, Zulkifli; Karunia, Leila; Kurnia Illahi, Rilci (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2024)
This article is action research as an alternative research method in empowering final-year student paper supervisor teachers. Action research is based on the assumption that research must be linked to change programs in assisted Islamic boarding schools. This research was carried out not only to obtain facts but also to create the desired conditions. Action research can be used effectively in research and action to empower final-year student paper supervisor teachers, because of its nature which emphasises the active participation of supervisor teachers. Through action research, it is possible to produce formulations that are adapted to the conditions of supervising teachers in carrying out efforts to increase information literacy competence in the context of completing final-grade student papers.